The Influence of Plant Growth-Stimulating Bacteria on the Glutathione-S-Transferase Activity and the Toxic Effect of the Herbicide Metsulfuron-Methyl in Wheat and Canola Plants - Darya Chetverikova; Margarita Bakaeva; Sergey Starikov; Aliya Kendjieva; Sergey Chetverikov (Toxics)
The ability of some rhizosphere bacteria to mitigate herbicidal stress in cultivated plants may be useful in agriculture and bioremediation. There is poor understanding of how bacteria directly or through herbicide degradation affect the biochemical processes in plants exposed to sulfonylurea herbicides. In this study, treatment with a combination of herbicide metsulfuron-methyl (MSM) and bacteria (Pseudomonas protegens DA1.2 or P. chlororaphis 4CH) of wheat (Triticum aestivum L.) and canola (Brassica napus L.) plants was carried out. Activity of glutathione-S-transferase (GST), an important enzyme for the herbicide detoxification, and acetolactate synthase (ALS), a target for MSM in plants, was measured by spectrophotometric assays. MSM residues were analyzed using the HPLC-MS. Then, 24 h after bacterial treatment, GST activity increased by 75–91% in wheat and by 38–94% in canola. On the 30th day, a decrease in MSM in the soil associated with bacterial treatment was 54.6–79.7%. An increase in GST activity and acceleration of MSM degradation were accompanied by a decrease in inhibition of the ALS enzyme in plants, which indicated a mitigation of the toxic effect. The results obtained are evidence that rhizospheric bacteria can have beneficial effects on plants exposed to MSM due to the combination of abilities to directly affect detoxification enzymes in plants and degrade MSM in the soil.